1996
DOI: 10.1097/00003246-199609000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating erythropoietin and interleukin-6 concentrations increase in critically ill children with sepsis and septic shock

Abstract: Plasma erythropoietin and IL-6 values are increased in critically ill children with sepsis or septic shock in comparison with controls. The data indicate that one or more plasma factors are responsible for stimulation of hypoxia-induced erythropoietin production in the Hep 3B cell line and suggest a possible role for IL-6 in the regulation of erythropoletin production in critically ill children with sepsis or septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…The circulating erythropoietin concentrations of septic adults in the current study (mean 124 IU/ml) is quite similar to the response seen in a recent study regarding septic children (mean 120 IU/ml) [6]. These circulating erythropoietin concentrations are approximately 6-fold higher than the 95th percentile concentrations reported in healthy adults and children without anemia, yet much lower than the erythropoietin concentrations measured in otherwise healthy adults and children with iron deficiency anemia.…”
supporting
confidence: 83%
“…The circulating erythropoietin concentrations of septic adults in the current study (mean 124 IU/ml) is quite similar to the response seen in a recent study regarding septic children (mean 120 IU/ml) [6]. These circulating erythropoietin concentrations are approximately 6-fold higher than the 95th percentile concentrations reported in healthy adults and children without anemia, yet much lower than the erythropoietin concentrations measured in otherwise healthy adults and children with iron deficiency anemia.…”
supporting
confidence: 83%
“…The expected inverse relationship between EPO levels and hemoglobin was present in survivors but not in nonsurvivors. Higher levels of EPO in nonsurvivors of septic shock were also noted by Nakamura et al (40) Nonanemic children with sepsis and septic shock have also been found to have increased EPO levels (41).…”
Section: Grade Bsupporting
confidence: 54%
“…9,10 Lipopolysaccharide (LPS) stimulation decreases erythropoiesis in rats because of reduced EPO synthesis. 11 However, in patients with septic shock, the endogenous serum EPO concentration is increased, 12,13 apparently independent of the hemoglobin concentration. 13 No relationship or a negative relationship was observed between serum EPO levels and blood hemoglobin concentrations in septic patients.…”
mentioning
confidence: 99%